The Healing Practice of Ustadz Akiluddin in Mamben Daya Village, Wanasaba District: A Living Qur’an Study of Surah Al-Isrā’ Verse 82 - Farah Haliyon Saniy; Lalu Abdul Gafar; Ahmad Khairul Affandi; Muhammad Daffa Noval Ghozi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study is motivated by the researcher’s interest in the healing practices of Ustadz Akiluddin in Mamben Daya Village, Wanasaba District. Generally, the Qur’an is used for reading, memorization, and as a guide for life. However, in this case, some members of the community use it as a means of healing. This alternative treatment has gained attention as many people seek other options after conventional medical treatments fail to bring improvement. One such alternative involves the use of Qur’anic verses combined with herbal remedies. Based on this background, the researcher formulated two research questions: (1) How is the healing practice using Qur’anic verses conducted, and which verses are used as a medium for healing by Ustadz Akiluddin? (2) What are the community’s perceptions of Ustadz Akiluddin’s healing practice, and what factors influence people to choose this method? This study is a Living Qur’an research employing a qualitative descriptive approach. The primary data sources are interviews with Ustadz Akiluddin and community members who are currently undergoing treatment or have been treated by him. Secondary data sources include books, journals, articles, theses, and other references related to this topic. The data collection techniques used in this research are observation, interviews, and documentation. The collected data were then analyzed through data reduction, data presentation, and drawing conclusions. The results of this study indicate that Ustadz Akiluddin treats certain common illnesses using verses from the Qur’an, along with other mediums such as water that has been inscribed with symbols and prayers, honey, young coconut, and various other herbal plants. The researcher also found that a portion of the community believes that Qur’anic verses can be used as a cure for all kinds of diseases. Factors that encourage people to choose this healing method include social influences and the specific conditions of the local community.